Sex differences in rates of permanent pacemaker implantation and in-hospital complications: A statewide cohort study of over 7 million persons from 2009-2018. - Vijayatubini Vijayarajan; Leonard Kritharides; David Brieger; Yeu-Yao Cheng; Vincent Chow; Austin Chin Chwan Ng (PLoS ONE, 2022)
Background Whether a bias exists in the implantation of permanent pacemakers (PPI) and complications according to sex and age in the Australian population is unclear. Hypothesis Population rate of PPI and its complications differed between men and women. Methods We examined the prevalence of PPI from January-2009 to December-2018 from datasets held by the New South Wales (NSW) Centre-for-Health-Record-Linkage, including patient's characteristics and in-hospital complications. All analysis was stratified by sex and age by decade. Results A total of 28,714 admissions involved PPI (40% women). The mean PPI rate (±standard-deviation) and median age (interquartile range) was 2,871±242 per-annum and 80yrs (73-86yrs), respectively. At the same time-period, the mean NSW population size was 7,487,393±315,505 persons (50% women; n = 3,773,756±334,912). The mean annual age-adjusted rate of PPI was 125.5±11.6 per-100,000-men, compared to 63.4±14.3 per-100,000-women (P<0.01). The mean annual rate of PPI increased from 2009-2017 by 0.9±3.3% in men, compared to 0.4±4.4% in women (P<0.01) suggesting a widening disparity. Total non-fatal in-hospital complications was higher in women compared to men (8.2% vs 6.6%, P<0.01), and this persisted throughout study period even after adjusting for multiple covariates. Overall, in-hospital mortality was low (0.73%) and similar between sexes. Conclusion In a statewide Australian population exceeding 7 million, PPI rates were consistently nearly two-fold higher for men compared to women over 10-years, with an apparently widening disparity, that was not explained by age. Overall complication rates were higher in women. Future studies should examine the aetiology behind this disparity in PPI rates, as well as its complications.